Determinan Pendapatan Usahatani Pepaya California vs Thailand: Studi pada Petani Skala Kecil - Sarifatun Nabila; Ari Septianingtyas Purwandhini; Qory Zuniana; Endang Wahyu Pudjiastuti; Deddy Kurniawan (Buletin Ilmiah Impas, 2026)
Papaya is one of the leading horticultural commodities in Indonesia, with California papaya and Thailand papaya being the two most widely cultivated and marketed varieties. This study aimed to analyze and compare the factors affecting farmers' income from California papaya and Thailand papaya farming in Mumbulsari District, Jember Regency. The research employed a quantitative approach using a survey method. Data were collected from 140 respondents consisting of 70 California papaya farmers and 70 Thailand papaya farmers selected through simple random sampling. Multiple linear regression analysis was used to identify the factors influencing farmers' income. The independent variables analyzed included production, selling price, seedlings, farming costs, education, and harvested area. The results showed that for California papaya farming, production, selling price, seedlings, and education had positive effects on income, whereas farming costs and harvested area had negative effects. However, none of these variables had a significant partial effect on income. The coefficient of determination (R²) indicated that only 20.7% of income variation could be explained by the variables included in the model. In contrast, for Thailand papaya farming, selling price and education positively affected income, while seedlings, farming costs, and harvested area had negative effects. Production, selling price, farming costs, and education significantly influenced income, with an R² value of 99.2%, indicating that nearly all income variation was explained by the variables analyzed. Simultaneously, all independent variables significantly affected farmers' income in both farming systems. The study concludes that the determinants of income differ between California and Thailand papaya farming, with Thailand papaya income being more strongly influenced by the analyzed variables than California papaya income.